Firearms: global perspectives on consequences, crime and control - Poole, Helen; Sneddon, Simon (Routledge, 2022)
"Firearms: Global Perspectives on Consequences, Crime and Control explores the many dimensions of the illicit use of firearms across the globe, including legal, social science, technical and research perspectives on the issue. Firearms will be of great interest to students of Criminology, Criminal Justice, International Law, International Development, Policing, Crime Control and Community Safety"--